Statistical modeling of microstructure evolution in a Ti-6Al-4V alloy during isothermal compression. (15th May 2021) - Hoar, Eric; Sahoo, Souvik; Mahdavi, Mostafa; Liang, Steven; Roy, Shibayan; Garmestani, Hamid
Abstract: A statistical continuum model is developed in the present study which uses microstructural information for a two-phase Ti-6Al-4V alloy to simulate the microstructure evolution during hot isothermal compression. Current models of microstructure prediction often use finite element methods. However, the statistical continuum model developed here does not rely onfinite element methods and thus can be performed much faster and with less computational resources without sacrificing prediction accuracy. This approach uses two-point statistics to describe the microstructural information related to phase distribution, grain size and phase/grain morphology. This formulation further utilizes the macroscopic strain-rate tensor to predict the deformation. The deformation is then used to calculate the resulting two-point statistics of the deformed microstructure. Finally, the simulated two-point statistics is compared to that experimentally obtained from scanning electron micrograph in backscatter electron mode i.e. SEM (BSE) images of the deformed microstructures. Graphical abstract: Image, graphical abstract